2013
DOI: 10.3389/fnagi.2013.00068
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Kyotorphin (Tyrosyl-Arginine) has Decreased Levels in the Cerebro-Spinal Fluid of Alzheimer’s Disease Patients: Potential Diagnostic and Pharmacological Implications

Abstract: In Alzheimer’s disease (AD), besides the characteristic deterioration of memory, studies also point to a higher pain tolerance in spite of sensibility preservation. A change in the normal tau protein phosphorylation is also characteristic of AD, which contributes to the pathogenesis of the disease and is useful in early diagnosis. Kyotorphin (KTP) is an endogenous analgesic dipeptide (Tyr-Arg) for which there is evidence of eventual neuroprotective and neuromodulatory properties. The objective of this work was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Kyotorphin is an endogenous analgesic dipeptide with potential neuroprotective properties. It has previously been found in rat brain tissue and human CSF samples [57, 58]. This is the first report of quantitative detection of kyotorphin in human serum.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Kyotorphin is an endogenous analgesic dipeptide with potential neuroprotective properties. It has previously been found in rat brain tissue and human CSF samples [57, 58]. This is the first report of quantitative detection of kyotorphin in human serum.…”
Section: Resultssupporting
confidence: 53%
“…Kyotorphin is proposed to have indirect opioid-like actions by modulating enkephalin release [59]. Kyotorphin does not cross the blood brain barrier, and is a candidate biomarker for neurodegenerative diseases such as Alzheimer’s disease [57]. While previous studies detected kyotorphin in CSF samples obtained from lumbar puncture, less invasive blood sample collection would be beneficial for patients, with subsequent detection as reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al reported that it has an inverse correlation with p-tau, and that p-tau/KTP values differ significantly between AD cases and controls [80] . Thus, KTP has potential utility in diagnosing AD.…”
Section: Kyotorphin (Ktp) Ktp Is An Endogenous Neuroprotectivementioning
confidence: 99%
“…Concerning the penetration of Blood-Brain Barrier (BBB) of KTP, the literature data are contradictory. The majority of research associated with KTP claimed that it has limited capacity to cross the BBB 48 . Some literature data showed that KTP was transported by H + -coupled peptide transporter PEPT2 [49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%